Constraints of Agri-Allied Sectors in Convergence of Extension Services in Four Major Indian States - Kareem, MA; Phand, Shahaji (Journal of Agricultural Extension Management, 2018)
Extension efforts in the Agri-Allied sectors are lacking effectiveness as these sectors viz, Sericulture, Fisheries, Animal Husbandry and Horticulture are not converging in their efforts. The present study was conducted in four major Indian states from four regions of the country. All the four allied sector departments were present and functioning in these states. The study was carried out to explore the constraints of allied sectors in convergence of extension services. The results from the study revealed that the major constraint in convergence was that, extension personnel were not trained to work in broad based extension and there was lack of understanding about why convergence is required. Lack of awareness, knowledge and understanding of broad based extension and absence of training in convergence were ranked the second major constraint in convergence faced by the officers followed by lack of policy guidelines, lack of interface for exchange of ideas, information and opinions. It was also found that frequent transfers and political compulsion were the least ranked constraints by the allied department staff. Widespread awareness and effective capacity building of the officers of agri-allied departments, formulation of clear policy guidelines and timely communication of information through modern Information and Communication Technology (ICT) with sufficient allocation of budget and other resources will facilitate the convergence process in delivering extension services of agri-allied departments.